Hyperelastic Behaviour of Auxetic Material in Tension and Compression Tests - Janus-Michalska Małgorzata (Technical Transactions, 2018)
This paper presents the numerical simulation of uniaxial tension and compression tests for negative Poisson’s ratio materials subjected to large strains. Numerical calculations are performed for the determination of the material characteristics of auxetic periodic lattices. The finite element method (FEM) coupled with 2D periodic homogenisation technique is used. The results show the existence of large variations in strain-stress plots, which can be achieved by changing the lattice geometry parameters.